2014
DOI: 10.5665/sleep.3936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Piezoelectric System as an Alternative to Electroencephalogram/ Electromyogram Recordings in Mouse Sleep Studies

Abstract: Mang GM, Nicod J, Emmenegger Y, Donohue KD, O'Hara BF, Franken P. Evaluation of a piezoelectric system as an alternative to electroencephalogram/electromyogram recordings in mouse sleep studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 32 publications
2
114
1
Order By: Relevance
“…While electroencephalographic (EEG) recording offers insight into sleep quality and stage, the piezoelectric sleep monitoring system offers a non-invasive approach to only quantify wakefulness and sleep durations, concordant with EEG analysis 41 . It is unclear how TBI or resolvin treatment may independently alter respiratory rate and confound the algorithmic detection of sleep, but we have previously demonstrated that the piezoelectric sleep system detects discrete bouts of 3 Hz breathing classified as sleep following mFPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While electroencephalographic (EEG) recording offers insight into sleep quality and stage, the piezoelectric sleep monitoring system offers a non-invasive approach to only quantify wakefulness and sleep durations, concordant with EEG analysis 41 . It is unclear how TBI or resolvin treatment may independently alter respiratory rate and confound the algorithmic detection of sleep, but we have previously demonstrated that the piezoelectric sleep system detects discrete bouts of 3 Hz breathing classified as sleep following mFPI.…”
Section: Discussionmentioning
confidence: 99%
“…The non-invasive sleep cage system (Signal Solutions, Lexington, KY) used in this study consisted of 16 separate units which simultaneously monitor sleep and wake states, as previously published 39-41 . Each cage unit housed a single mouse inside 18 × 18 centimeter walled compartments with attached food and water structures 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Piezo foil PVDF based circadian rhythm scoring of sleep/wake rhythm was used as established in Donohue et al (2008), and further used in AD studies (Duncan et al, 2012; Mang et al, 2014; Sethi et al, 2015). Mice were individually housed for 5 days in clean plastic cages (Signal Solutions LLC) with ~5 mm of corn cob bedding lining the floor and lined with the PVDF foil.…”
Section: Methodsmentioning
confidence: 99%
“…The piezo system (Signal Solutions, LLC, Lexington, Kentucky, USA) is described in detail elsewhere (Donohue et al 2008; Mang et al 2014). Briefly, the piezo sensor is a thin dielectric sheet that generates a voltage signal in response to changes in surface pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting quasirhythmic “piezo” signal differentiates sleep from quiet or active wakefulness with accuracy comparable to a human observer (Donohue et al 2008). Mang et al (2014) found that the decision statistic used by the same classifier to distinguish sleep from wakefulness (Donohue et al 2008) appears to change in value following REM - NREM transitions as well. Sato et al (2010) used a piezoelectric transducer to monitor mice and documented rapid increases in breathing rate during sleep with atonic posture, presumably in REM .…”
Section: Introductionmentioning
confidence: 99%